2018
DOI: 10.1002/stc.2194
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for the identification of multiple cracks on beams and frames by static measurements

Abstract: In this work a model of the Euler-Bernoulli beam in presence of multiple concentrated open cracks, based on the adoption of a localized flexibility model, is adopted. The closed form solution in terms of transversal displacements due to static loads and general boundary condition is exploited to propose an inverse damage identification procedure. The proposed identification procedure does not require any solution algorithm, on the contrary is formulated by means of simple explicit sequential expressions for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Liu et al [14] presented a method for structural damage detection of statically loaded structures based on the change of internal force and displacement of the finite element model. Caddemi et al [15] successfully identified the local damage of Euler-Bernoulli beams based on static loads and boundary conditions under the interference of environmental noise. However, these studies based on static characteristics still have some shortcomings, such as the cost being high and the response data being easily disturbed by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [14] presented a method for structural damage detection of statically loaded structures based on the change of internal force and displacement of the finite element model. Caddemi et al [15] successfully identified the local damage of Euler-Bernoulli beams based on static loads and boundary conditions under the interference of environmental noise. However, these studies based on static characteristics still have some shortcomings, such as the cost being high and the response data being easily disturbed by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic ambient tests can be a valuable aid in calibrating FEM models to be used for the analyses [23], and they can also bring different behaviours of the various parts of complex buildings or blocks of houses to the forefront [24]. Similar techniques are employed in dynamic damage detection methods for structural health purposes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…While the latter studies are limited to considering cracked FGM beams, this study is devoted to multiple cracked identification in frames made of FGM using the technique proposed in (Lien et al, 2019a) for multi-span beams. Cracked frame structures were considered in (Khiem, 2006;Caddemi and Caliò, 2013;Caddemi et al, 2018), but they consisted of cracked homogeneous Euler-Bernoulli beam elements. In this paper, first, we establish the dynamic stiffness model of a cracked FGM frame based on an explicit exact solution of free vibration in a multiple cracked FGM beam element.…”
Section: Introductionmentioning
confidence: 99%